The Impact of Corporate Social Responsibility and Environmental Performance to Improve Return on Asset in Manufacturing Company - Riauli Susilawaty Hutapea (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
In Indonesia there are so many companies in manufacturing sector that do not process hazardous toxic waste (B3) properly, so that environmental pollution continues to occur. The Ministry of Industry and the Ministry of Environment and Forestry are targeting to reduce waste by up to 70%, and create a green industry. To support this target, the Ministry of Industry introduced a circular economy with 5 main principles, namely, reduce, reuse, recycle, recovery, and repair. These 5 principles already exist in the CSR (Corporate Social Responsibility) indicator which has been standardized by the GRI (Global Reporting Initiative) created by the GSSB (Global Sustainability Standards Board), so companies are obliged to apply them. This CSR will be shown in the company's annual Sustainability Report. There is an additional program to support environmental responsibility, namely PROPER (Company Performance Rating Program in Environmental Management). PROPER as an indicator that must be carried out by companies to manage production waste. Creating a green industry and a green environment will have a positive impact on the company, by increasing profitability. Company profitability can be measured by ROA, so that investors can see how the company manages assets to generate profit even though it incurs high costs to manage waste. The purpose of this study is to measure how significant the influence of CSR and environmental performance is on the profitability of manufacturing sector companies listed on the Indonesia Stock Exchange for the 2021 period.